2020
DOI: 10.1111/ans.16060
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rate of colorectal cancer in younger patients: a review of colonoscopy findings in patients under 50 at a tertiary institution

Abstract: Background: In Australia, colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer death. It is more common in patients over 50 years, with previous evidence showing patients under 50 years account for only 9% of CRC. However, recent Australian and International studies have shown an increase in CRC incidence in patients under 50 years of age. The main aim of this study was to analyse the incidence of CRC in patients under 50 and to determine if screening would be benefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Our findings demonstrate that a substantial proportion of patients below the routine average risk screening age of 50 years have potentially premalignant SSLs that may contribute to the burden of CRC long-term. Therefore, while recent studies support earlier initiation of FIT for increasing CRC rates in younger patients, 3 our findings suggest that this may not provide adequate protection for females under 50 years who have considerable rates of SSLs. Our study thus raises the question of whether CRC screening using specifically colonoscopy should be considered for Caucasian women aged < 50 years.…”
Section: Should the High Prevalence Of Sessile Serrated Lesions In Patients Aged Below 50 Years Influence Screening Colonoscopy Recommendcontrasting
confidence: 81%
See 1 more Smart Citation
“…Our findings demonstrate that a substantial proportion of patients below the routine average risk screening age of 50 years have potentially premalignant SSLs that may contribute to the burden of CRC long-term. Therefore, while recent studies support earlier initiation of FIT for increasing CRC rates in younger patients, 3 our findings suggest that this may not provide adequate protection for females under 50 years who have considerable rates of SSLs. Our study thus raises the question of whether CRC screening using specifically colonoscopy should be considered for Caucasian women aged < 50 years.…”
Section: Should the High Prevalence Of Sessile Serrated Lesions In Patients Aged Below 50 Years Influence Screening Colonoscopy Recommendcontrasting
confidence: 81%
“…The data presented demonstrated that although SLs were detected more frequently in older patients, one in six (16.9%) of SLs were detected in patients aged 40-49, which is below the minimum age for many CRC screening programs. These findings challenge the current paradigms of CRC screening programs, particularly when viewed in the context of the new risk classification for SLs (which establish their malignant potential), rising rates of CRC in patients < 50, 3 the fact that fecal immunochemical tests (FIT) are not sensitive for detection of sessile serrated lesions (SSLs), 4 and recent US recommendations lowering the CRC screening age to 45 years. 5 We would like to share our observations from a cross-sectional examination of 2164 patients from a predominantly Caucasian, general colonoscopy population in Perth, Australia, in 2019.…”
Section: Should the High Prevalence Of Sessile Serrated Lesions In Patients Aged Below 50 Years Influence Screening Colonoscopy Recommendmentioning
confidence: 95%
“…Significantly, FIT status was not associated with SSL detection, consistent with the fact that SSLs rarely bleed [4,16]. This means that while some studies support earlier initiation of FIT for increasing rates of CRC in average-risk patients < 50 years, such an approach may provide inadequate protection for females < 50 years who may be more susceptible to SSLs [3]. Whether there are specific characteristics that would justify screening with colonoscopy in females < 50 years remains to be explored.…”
Section: Colonoscopy Indicationmentioning
confidence: 82%
“…Reasons for this variability are similar to those regarding sex. A recent Australian study by Kim et al [3] identified rising CRC rates in patients aged < 50 years, particularly in males. Furthermore, another recent paper by Sehgal et al [30] concluded that colonoscopy at ages 45-49 was associated with a considerable decrease in CRC incidence in both males and females.…”
Section: Age and Sexmentioning
confidence: 99%
See 1 more Smart Citation